A Dynamic simulator for the management of disorders of the body water metabolism - Karanfil, Özge. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
Regulation of the body water and its appropriate distribution between compartmentsnecessitates an understanding of two homeostatic systems: the system that regulates theextracellular (EC) sodium concentration/body water content and the system that regulates the blood volume/sodium content. The main feedback system for body water regulation isthe Antidiuretic Hormone (ADH)-thirst system, and the main feedback mechanisms forsodium balance include the Aldosterone and the Atrial Natriuretic Hormones, and the renalmechanisms. In ADH-induced hyponatremia, both the ADH and the thirst feedback loops are dysregulated, and the result is a lower sodium concentration and higher body watercontent, which may cause serious consequences.In this study, a simulation model is built using system dynamics methodology tostudy the body water regulation and its disorders by focusing on the fundamental feedback mechanisms in the normal and disease physiology. This model is then extended to includerelated therapeutic interventions of a particular body water disorder, namely waterintoxication/ hyponatremia, and a game version is produced to test the possible effects of agiven set of treatment options on a simulated patient. The model is shown to adequately reproduce the changes in the body fluid balance not only in a normal person as a result of agiven disturbance, but also in a hypothetical hyponatremia patient. The interactivesimulation game version of the model proves to be a useful experimental platform todescribe changes known to occur after administration of various pharmacological means. The aim of the treatment is to increase the EC sodium concentration safely by reducing thebody water and replenishing the sodium deficits. Game results demonstrate that hypertonicsaline should be given carefully concurrently with drugs that increase urine flow, andADH-Antagonists happened to be superior over diuretics. The model and the game version constitute an experimental laboratory for a closed-loop therapy approach to hyponatremia.
Keywords: Body fluids.; Simulation methods.